Eradicating polio in Pakistan: an analysis of the challenges and solutions to this security and health issue. Issue 1 (December 2016) - Hussain, Shoaib; Boyle, Peter; Patel, Preeti; Sullivan, Richard
Abstract Since the launch of the Global Polio Eradication Initiative (GPEI) in 1988 the global incidence of poliomyelitis has fallen by nearly 99 %. From a situation where wild type poliovirus was endemic in 125 countries across five continents, transmission is now limited to regions of just three countries – Pakistan, Afghanistan and Nigeria. A sharp increase in Pakistan's poliomyelitis cases in 2014 prompted the International Health Regulations Emergency Committee to declare the situation a 'public health emergency of international concern'. Global polio eradication hinges on Pakistan's ability to address the religious, political and socioeconomic barriers to immunisation; including discrepancies in vaccine coverage, a poor health infrastructure, and conflict in polio-endemic regions of the country. This analysis provides an overview of the GPEI, focusing on the historical and contemporary challenges facing Pakistan's polio eradication programme and the impact of conflict and insecurity, and sheds light on strategies to combat vaccine hesitancy, engage local communities and build on recent progress towards polio eradication in Pakistan.